Are medical treatments for individuals and groups like single-play and multiple-play gambles? - Michael L. DeKay; John C. Hershey; Mark D. Spranca; Peter A. Ubel; David A. Asch (Judgment and Decision Making, 2006)
People are often more likely to accept risky monetary gambles with positive expected values when the gambles will be played more than once. We investigated whether this distinction between single-play and multiple-play gambles extends to medical treatments for individual patients and groups of patients. Resident physicians and medical students (n = 69) and undergraduates (n = 99) ranked 9 different flu shots and a no-flu-shot option in 1 of 4 combinations of perspective (individual patient vs. group of 1000 patients) and uncertainty frame (probability vs. frequency). The rank of the no-flu-shot option (a measure of preference for treatment vs. no treatment) was not significantly related to perspective or participant population. The main effect of uncertainty frame and the interaction between perspective and uncertainty frame approached significance (0.1 > p > 0.05), with the no-flu-shot option faring particularly poorly (treatment faring particularly well) when decisions about many patients were based on frequency information. Undergraduate participants believed that the no-flu-shot option would be less attractive (treatment would be more attractive) in decisions about many patients, but these intuitions were inconsistent with the actual ranks. These results and those of other studies suggest that medical treatments for individuals and groups are not analogous to single-play and multiple-play monetary gambles, perhaps because many people are unwilling to aggregate treatment outcomes over patients in the same way that they would compute net gains or losses over monetary gambles.